Adistemia watsoni: a stored product fungus beetle new record for Greece - Papadopoulou, Sm. Ch.; Buchelos, C. Th. (ENTOMOLOGIA HELLENICA, 2011)
During an inspection survey concerning stored product insects in the mainland Greece the stored product fungus beetle Adistemia watsoni Wollaston (Coleoptera: Lathridiidae) was recorded to feed upon conidia of Penicillium developing on stored plums and corn. Information on its morphology and distribution is briefly given.